Методичні положення встановлення нижньої межі ціни інтелектуальної технології - Косенко, Олександра Петрівна (НТУ ХПІ", 2014)
Розроблено пропозиції щодо визначення мінімального рівня ціни на об’єкти інтелектуальної власності. Ці ціни можуть бути використані як фінальна позиція при проведенні перемовин між розробником (продавцем і потенційним споживачем інтелектуальних технологій на предмет здійснення технологічного трансферу (комерціалізації технологій).

Developed proposals to determine the minimum level of prices of the objects of intellectual property. These rates can be used as the final position in negotiations between the developer (seller and potential consumer of intelligent technologies to perform technology transfer (technology commercialization). In the article it is proved that the practical use of the expert-analytical or analytical and computational level determine the minimum rates of intellectual technology depends on the available information on production and business activities of the developer and the potential consumer of intelligent technology and its degree of precision and accuracy; available information on technical and economic characteristics of the intellectual product; the required accuracy of calculations and the scope of their practical use. According to the author, in most cases, a model is developed to determine the minimum price for the intellectual property provides reasonable results with a sufficient degree of precision may be used in determining prices for technology products.
Methodological provisions establishing the lower price limit intellectual technology
Keywords: ринковий механізм; об'єкти інтелектуальної власності; фактори впливу; комерціалізації технологій; розробник; споживач; factors of influence; intellectual technology; commercialization; developer; consumer; price